Bacterial contamination of healthcare worker's mobile phones: a case study at two referral hospitals in Uganda. Issue 1 (31st December 2022) - Tusabe, Fred; Kesande, Maureen; Amir, Afreenish; Iannone, Olivia; Ayebare, Rodgers Rodriguez; Nanyondo, Judith
ABSTRACT: Hospital and community-acquired infections are escalating and pose significant public health unhealthiness worldwide. The advancements of telemedicine and automation of healthcare records are supported by cellphones, laptops and wearable devices. This study focused on the incidence of healthcare workers' mobile phones becoming contaminated with pathogenic bacteria and their possible roles as vehicles of transmission of antimicrobial-resistant bacteria. A case study at two referral hospitals in Uganda between May and October 2020. Self-administered questionnaires were administered to participants after informed consent. Mobile phones of the participants in different departments of the hospitals were swabbed and samples were collected and transported to the microbiology laboratory for bacterial culture and antimicrobial susceptibility tests. The point prevalence of Healthcare workers' mobile phone bacterial contamination with one or more species was 93%. Organisms isolated were E. coli 5.6% (1), Micrococcus spp 11.1% (2), Coagulase-negative staphylococci, CoNS, 61.1% (11) and Bacillus spp 22.2% (4). About 45% of the organisms were multidrug-resistant. Resistance was major to penicillin, cotrimoxazole, ciprofloxacin and Gentamicin, respectively. The isolated E. coli was resistant to all antibiotics used in the study. Only 15% (2) of the participants disinfected their phones at least once a week and 8% cleaned their hands after using a mobile phone. Healthcare Workers' mobile phones can act as fomites for the transmission of multidrug-resistant microorganisms. This study provides strong evidence for developing and strengthening disinfection protocols for mobile phones and does not underscore the importance of hand hygiene in the middle of a patient encounter especially when the HCW grabs a phone but doesn't re-clean their hands before patient contact. Abbreviations: MDR, Multidrug-resistant; WHO, World Health Organization; IPC, infection prevention and control; HHC, hand hygiene compliance; JMEDICC, Joint Mobile Emerging Disease Intervention Clinical Capability